STUDY ON ANTIMYCOBACTERIAL ACTIVITY OF MARINE ACTINOMYCETES FROM COROMONDAL COASTAL REGION OF SOUTHERN INDIA - GAJALAKSHMI, P.; Raja, A.; James, R. Arthur (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The objective of the present study is to screen the novel actinomycetes from marine sediment active against mycobacterium sp. Methods: actinomycetes were isolated by crowded plate technique and its antimycobacterial activity was determined by stroke method followed by optimized fermentation. The active fraction was extracted and bio assayed by TLC. Results: Totally 25 actinomycetes were isolated from 9 Marine sediment samples and frequency of isolates were, 40% of Streptomyces sp (ECRST) 32% of Micromonospora(ECRMM), 16% of Micropolyspora (ECRMP) and 12% were Streptoverticillium (ECRSV). Among the 25 isolates Microployspora a rare actinobacteria designated as ECRMP 4 showed potent antimycobacterial activity against M.tuberculosis. The zone of inhibition was 20 Â± 0.1mm and the percentage of relative inhibitory zone was 62 against M.tuberculosis. The bioassay of crude compound prevails that the Rf value of compound is 0.16. Conclusion: The present study concludes that the isolated marine Micropolyspora capable to produce noval antimycobacterial compound effective against M.tuberculosis.